Betulinic Acid Inhibits Endometriosis Through Suppression of Estrogen Receptor β Signaling Pathway - Xiang, Dongfang; Zhao, Min; Cai, Xiaofan; Wang, Yongxia; Zhang, Lei; Yao, Helen; Liu, Min; Yang, Huan; Xu, Mingtao; Li, Huilin; Peng, Huijuan; Wang, Min; et al. (Frontiers in Endocrinology, 2020)
Endometriosis is an inflammatory gynecological disorder characterized by endometrial tissue growth located outside of the uterine cavity in addition to chronic pelvic pain and infertility. In this study, we aim to develop a potential therapeutic treatment based on the pathogenesis and mechanism of Endometriosis. Our preliminary data showed that the expression of estrogen receptor β (ERβ) was significantly increased, while ERα was significantly decreased, in endometriotic cells compared to normal endometrial cells. Further investigation showed that betulinic acid (BA) treatment suppressed ERβ expression through epigenetic modification on the ERβ promoter, while had no effect on ERα expression. In addition, BA treatment suppresses ERβ target genes, including superoxide dismutase 2 (SOD2), nuclear respiratory factor-1 (NRF1), cyclooxygenase 2 (COX2) and matrix metalloproteinase-1 (MMP1), subsequently increasing oxidative stress, triggering mitochondrial dysfunction, decreasing elevated proinflammatory cytokines, and eventually suppressing endometriotic cell proliferation, mimicking the effect of ERβ knockdown. On the other hand, gain of ERβ by lentivirus infection in normal endometrial cells resulted in increased cell proliferation and proinflammatory cytokine release, while BA treatment diminished this effect through ERβ suppression with subsequent oxidative stress and apoptosis. Our results indicate that ERβ may be a major driving force for the development of endometriosis, while BA inhibits Endometriosis through specific suppression of the ERβ signaling pathway. This study provides a novel therapeutic strategy for endometriosis treatment through BA-mediated ERβ suppression.